2005
DOI: 10.1038/sj.eye.6701852
|View full text |Cite
|
Sign up to set email alerts
|

Drusen classification in bilateral drusen and fellow eye of exudative age-related macular degeneration

Abstract: Aim To assess the value of the modified international classification system in screening high-risk patients with bilateral age-related maculopathy (ARM) from those with lower risk characteristics. Methods In total, 164 digital images of 106 patients with either bilateral ARM (group A) or the fellow eyes of unilateral exudative age-related macular degeneration (AMD) (Group B) were included. Patients with no signs of ARM in both eyes or those with bilateral late AMD were excluded. The images were randomised and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Hamada et al [34] reported that eyes with large drusen found in the inner circle of the Wisconsin template showed a higher probability of having associated geographic atrophy. The combination of FAF imaging with other imaging modalities, such as fluorescein angiography (FA) and SD-OCT, may provide additional prognosticating data for interpreting the status of drusen in dry AMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hamada et al [34] reported that eyes with large drusen found in the inner circle of the Wisconsin template showed a higher probability of having associated geographic atrophy. The combination of FAF imaging with other imaging modalities, such as fluorescein angiography (FA) and SD-OCT, may provide additional prognosticating data for interpreting the status of drusen in dry AMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these differences are not immediately apparent and merit further investigation. However, our observation that the prevalence of AMD was similar in our sample to that reported for other populations may suggest that earlier grades of ARM are not always accurate indicators of progression to AMD, as has been suggested previously 27. It should also be noted that, in our study, grading was initially performed in each participating centre, as this may have resulted in differences compared with studies in which all images were centrally graded.…”
Section: Discussionmentioning
confidence: 40%
“…Em estudo realizado em (1) , um microscópio Carl Zeiss ® (9) teve seu sistema de iluminação adaptado para o RGB (do inglês, "Red, Green and Blue"), possibilitando a visualização de amostras de tecidos biológicos com diferentes intensidades de cores, proporcionando realces diferenciados das estruturas do tecido de acordo com o comprimento de onda aplicado. Trabalhos relacionados à medicina oftálmica utilizam téc-nicas de retinografia colorida e "red free", para realce de contraste em imagens de fundo de olho visando o estudo de patologias (10)(11) . Em oftalmologia, o exame denominado retinografia colorida ilumina o polo posterior com luz de comprimento de onda na região do visível do espectro e a imagem da retina pode ser capturada através de fotografia ou filmagem, dependendo do tipo de equipamento (12) .…”
Section: Resumo Introduçãounclassified